Simulated Patient Perceptions of Telemedicine Medical Interviews: Extending the Calgary–Cambridge Framework in Digital Consultations - Leila Mona Ganiem; Wawang Setiawan Sukarya; Ade Solihat; Rafik Hani (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Background: Telemedicine has transformed healthcare delivery by enabling remote doctor–patient interaction; however, digitally mediated consultations may alter communication processes and reduce relational engagement during medical interviews. Existing communication frameworks such as the Calgary–Cambridge model were originally developed for face-to-face consultations and may require adaptation for telemedicine contexts. Objective: This study aimed to examine how communication processes unfold across telemedicine consultations using the Calgary–Cambridge framework as an organizational structure, and to identify emergent communication challenges from the perspective of simulated patients. Method: A qualitative descriptive design involving 30 first-year medical students acting as simulated patients across 120 telemedicine consultations in Indonesia. Data were collected through structured post-consultation reflections and an interview with a telemedicine platform coordinator. Thematic analysis was conducted inductively, with consultation stages serving as sensitizing categories for data organization. Result: Six emergent communication themes were identified: (1) relational deficit, (2) modality mismatch, (3) diagnostic risk, (4) information asymmetry, (5) limited patient involvement, and (6) unresolved communication. Consultations tended to prioritize biomedical information exchange over relational communication. Simulated patients responded more positively when doctors demonstrated explicit verbal empathy, comprehensive information gathering, adaptive use of voice or video communication, clear explanations, and supportive consultation closure. In contrast, reliance on text-based interaction, limited explanation, and physician-centered decision-making negatively affected participant experiences. Conclusion: Telemedicine consultations reshape doctor–patient communication and require contextual adaptation of the Calgary–Cambridge framework. Effective telemedicine communication requires stronger emphasis on explicit rapport-building, modality management, structured verbal clarification, and facilitation of patient participation within digitally mediated healthcare interactions